A highly fluorescent metal organic framework probe for 2, 4, 6-trinitrophenol detection via post-synthetic modification of UIO-66-NH2. (August 2019) - Tang, Yilong; Wu, Huafeng; Chen, Jinming; Jia, Jinlan; Yu, Jinping; Xu, Wei; Fu, Yanyan; He, Qingguo; Cao, Huimin; Cheng, Jiangong
Abstract: Metal organic frameworks (MOFs) have been hotly concerned due to their unique structure and properties. A new highly fluorescent MOF was developed via post-synthesis of UIO-66-NH2 through an efficient click reaction with 1-ethynylpyrene for the 2, 4, 6-trinitrophenol (PA) detection which named UIO-66-Py. It exhibited a significantly enhanced fluorescence intensity than UIO-66-NH2 and showed excellent selectivity and sensitivity for sensing PA in solution via the fluorescence quenching mechanism. The UIO-66-Py showed an 85% fluorescence quenching efficiency with 0.203 mM PA and the detection limit was 4.5 × 10 −7 M. The excellent selectivity of the probe was ascribed to the hydrogen bond interaction between UIO-66-Py and PA as evidenced by FT-IR. The hydrogen bond interaction promoted the photo-induced electron transfer (PET) between UIO-66-Py and PA which leading to the better selectivity of UIO-66-Py for PA detection over TNT. This post-synthetic modification idea provided a strategy for the development of MOFs with multifunctional sensing. Graphical abstract: A new highly fluorescent metal organic framework probe (UIO-66-Py) exhibits the excellent selectivity and sensitivity towards PA detection as the hydrogen bonding interaction and hence an efficient photo-induced electron transfer, the detection limit of PA is 4.5 × 10 −7 M. Image 1 Highlights: A new fluorescent MOF probe (UIO-66-Py) was obtained via post-synthesis through an click reaction for PA detection. UIO-66-Py exhibits an excellent selectivity and sensitivity to PA in THF, the detection limit of PA is 4.5 × 10 −7 M. A promising design strategy for the synthesis of high efficient fluorescent MOFs for dangerous chemical detection.